1932
DOI: 10.6028/jres.008.058
|View full text |Cite
|
Sign up to set email alerts
|

The isoelectric point of wool

Abstract: Suspensions of solvent-extracted Idaho and Australian raw wool and of scoured worsted cloth in buffer solutions of different pH were prepared by grinding the dry wool to a fine powder and shaking the powder in the buffer solution. Electrophoretic measurements of these suspensions gave an isoelectric point for each wool at pH 3.4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1938
1938
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The total nitrogen contents of the preparations appear to bear no direct relation to their isoelectric points. This same result with wool was noted by Harris [12] in 1932, who found that a difference of 1 percent in nitrogen content did not result. in different isoelect,ric points.…”
Section: Amide Nitrogen Content Andsupporting
confidence: 84%
See 1 more Smart Citation
“…The total nitrogen contents of the preparations appear to bear no direct relation to their isoelectric points. This same result with wool was noted by Harris [12] in 1932, who found that a difference of 1 percent in nitrogen content did not result. in different isoelect,ric points.…”
Section: Amide Nitrogen Content Andsupporting
confidence: 84%
“…A practical application of the cell in the investigation of wool protein is given by Harris [12]. The microscope was used with an 8-mm objective and a 20 X eyepiece.…”
Section: Electrophoretic Analysismentioning
confidence: 99%
“…It will be necessary to include in the development of a complete theory of the effect of pH on the electric mobilities of crystalline amino acids, the effect of adsorbed hydrogen ions in addition to the entrance of dissolved amino acid molecules into the surface, even though the effects of hydrogen ions may be less important than isomorphous ions. In the case of the surfaces of the keratins, such as wool (25), hair, skin, and finger nails (26), the electrokinetic properties are probably influenced more than adsorbed proteins by the constraints occurring at the surface of the crystal lattice. Since in the case of the keratins the elongated protein molecules are arranged side by side and held together by S--S linkages for the most part (27,28), it seems likely that the constraints imposed on the reacting groups of the sur-ELECTROKINETIC PHENOMENA.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the negative effect for leaching of PFAS species in the presence of multivalent cations in landfill leachate could be due to the cations acting as bridges between negatively charged PFASs and negatively charged carpet surfaces (i.e., [carpet surface] − + Ca 2+ + R-COO − or R-SO 3 − ). This mechanism results from the pK a of PFASs (PFCAs (<0.52) and PFSAs (< −3.26)) and the net carpet charge of zero for pH 3.4 according to Harris,42 which is less than the leachate pHs studied.…”
Section: ■ Results and Discussionmentioning
confidence: 99%